Analysis of the Age Replacement Method to Reduce Tool Downtime - Sukendar, Irwan; Syakhroni, Akhmad; Prawira, Muhammad Reza (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
A manufacturing company engaged in the manufacturing of diesel engines in Indonesia has a problem with high downtime. The most frequent replacement frequency is in the cylinder liner line which in April - June 2018 has 1254 units of replacements, besides that the cylinder liner line also has the highest downtime of 7243.94 minutes. To overcome this problem, it is necessary to schedule tool replacement using the Age Replacement method, where this method is to determine the tool replacement schedule with the least downtime. After that the calculation is done using the Availability method, where the higher the Availability value of a tool, the better the condition of the tool to operate according to its function. And finally the calculation is done using the Reliability method, where the higher the value of the reliability of a tool, the less likely the damage will occur to the tool.